2016
DOI: 10.1074/jbc.m115.713545
|View full text |Cite
|
Sign up to set email alerts
|

The Deubiquitinase Inhibitor PR-619 Sensitizes Normal Human Fibroblasts to Tumor Necrosis Factor-related Apoptosis-inducing Ligand (TRAIL)-mediated Cell Death

Abstract: TNF-related apoptosis-inducing ligand (TRAIL) is a potential cancer therapy that selectively targets cancer cell death while non-malignant cells remain viable. Using a panel of normal human fibroblasts, we characterized molecular differences in human foreskin fibroblasts and WI-38 TRAIL-resistant cells and marginally sensitive MRC-5 cells compared with TRAILsensitive human lung and colon cancer cells. We identified decreased caspase-8 protein expression and protein stability in normal fibroblasts compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…They found that treatment of fibroblasts with a neutralising antibody to TGFβ1 inhibited TRAIL-mediated collagenα2a gene expression and total collagen secretion, implying a TRAIL-TGFβ1-collagen axis (42). While fibroblasts express all TRAIL receptors (43,44), it is unclear whether the TRAIL-TGFβ1-collagen axis involves a specific receptor. These suggest that TRAIL may contribute to the regulation of tensile strength in the blood vessel wall, in part, by regulating synthesis of collagen.…”
Section: Trail and Ecm Componentsmentioning
confidence: 99%
“…They found that treatment of fibroblasts with a neutralising antibody to TGFβ1 inhibited TRAIL-mediated collagenα2a gene expression and total collagen secretion, implying a TRAIL-TGFβ1-collagen axis (42). While fibroblasts express all TRAIL receptors (43,44), it is unclear whether the TRAIL-TGFβ1-collagen axis involves a specific receptor. These suggest that TRAIL may contribute to the regulation of tensile strength in the blood vessel wall, in part, by regulating synthesis of collagen.…”
Section: Trail and Ecm Componentsmentioning
confidence: 99%
“…Subsequently, we tested the effect of modifications of Sox2 level on NPCs differentiation by chemical perturbations of the UB/DUB system. Given that the specific inhibitor targeting CUL4A DET1-COP1 or OTUD7B is unavailable, we used unspecific DUB inhibitors PR-619 37 , b-AP-15 38 , and the inhibitor of NEDD8-activating enzyme (NAE) MLN4924 which had been demonstrated to suppress neddylation of Cullins, and inactivate Cullin-RING ligases 39 . The results showed that compared with control, the treatment of MLN4924 promoted NPC maintenance marked by increased Sox2 level and decreased neuN level, while PR-619 and b-AP-15 enhanced cell differentiation marked by decreased Sox2 level and increased neuN level (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here, certain agents were used to improve the sensitivity of the cells to TRAIL-induced apoptosis, whereas TRAIL was responsible for the promotion of cancer cell apoptosis. 15 Studies have consistently found that several compounds and agents can improve the sensitivity of cells to TRAIL-induced apoptosis; these are defined as anticancer agents. Among them, Andro, a diterpenoid lactone compound from Andrographis paniculata, is a type of anticancer agent which is currently being widely researched.…”
Section: Discussionmentioning
confidence: 99%